Open-Bin Composting for Enhancing the Processed Fecal Sludge Quality with Co-Composting Materials as Admixture - Lucky Caesar Direstiyani; Fernando Gouw; Mochamad Adhiraga Pratama (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Processed fecal sludge generated from a sludge treatment plant rich of organic content, micronutrients, and several heavy metals that might potentially exist. Composting process recognized as a promising and cost-effective method to improve the sludge quality. The composting process was carried out in this study by using modified Compost Bag with processed sludge from fecal sludge treatment plant as the main material and organic waste and dry leaves as co-composting materials. The macro-micronutrients and heavy metal concentration of the produced compost were further analyzed. The potential application was also considered by indulging the risk assessment. The main and co-composting materials were investigated in three different ratios of processed fecal sludge (S), organic waste (OW), and dry leaves (DL) to get the optimum composition that meet the compost quality standard. Compost R2 with the ratio of 50S: 25OW: 25DL as an optimum composition which resulted good quality compost with the C/N ratio of 10.29, Total P2O5 about 2.45%, Total K2O of 0.38%, and the Cu removal up to 91.17%. The produced Compost R2 has met the compost quality standard with Hazard Quotient (HQ) for non-carcinogenic effects less than 1 revealed no potential for disease-causing effects thus safe to be used in daily life.